The Effect Of Financial Ratios On The Price Of Shares Listed On The Jakarta Islamic Index For The Period 2020-2024 - Adi Musakir; Titin Agustin Nengsih; Achyat Budianto (International Journal of Business and Quality Research, 2026)
This study aims to determine the influence of current ratio, debt to equity ratio and total asset turnover partially or simultaneously on stock prices. The method in this study uses a quantitative method. The sample selection process is using the purposive sampling technique, which is the determination of samples with certain criteria, the sample used by companies listed in the Jakarta Islamic Index for the 2020-2024 period. Based on the purposive sampling method, there are 16 companies that meet the criteria. The data type used is the data type of the panel. The data analysis technique used panel data regression, classical assumption tests (normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test), hypothesis test (t-test and F-test) and determination coefficient (r-square). The results of the study prove that partially the current ratio has no effect on the stock price, while the debt to equity ratio has a significant effect on the stock price, while the total asset turnover has a significant effect on the stock price, simultaneously the current ratio, debt to equity ratio and total asset turnover have a significant effect on the stock price.